The future of pharmaceutics: 3D-printing? - Kinga Ilyés (Romanian Journal of Pharmaceutical Practice, 2020)
Cephalosporins Over the last century pharmaceutical technology has progressed at an exponential rate, starting off from powder formulation, progressing through tablets, capsules, all the way the nano drug delivery systems. The industrial manufacturing appeared as a result to the increasing demand from the market. Large scale manufacturing setups relied on the one size fits all principle, aiming to serve the populational rather than individual needs. However, there are certain population groups (pediatric, geriatric, poly-medicated etc.) in need of special therapeutic adaptations. Three-dimensional printing (3D-printing, 3DP), due to its versatility and flexibility, can be considered a form of personalized medicine. Dose, release and form, by means of design, can be adapted based on individual needs and preferences, that ultimately can increase therapeutic outcomes, while bringing the manufacturing closer to the patient.